Lasalliapustulata lichen as possible natural antigenotoxic, antioxidant, antimicrobial and anticancer agent - Kosanić, Marijana (Cytotechnology, 2015)
The methanol extract of the lichen Lasallia pustulata was tested for genotoxic, antioxidant, antimicrobial and anticancer activities. We did this using a cytokinesis block micronucleus (MN) assay on peripheral blood lymphocytes, by measuring free radical and superoxide anion scavenging activity, reducing power, determining of total phenolic compounds and determining the total flavonoid content, measuring the minimal inhibitory concentration by the broth microdilution method against five species of bacteria and five species of fungi and by using the microculture tetrazolium test on FemX (human melanoma) and LS174 (human colon carcinoma) cell lines. As a result of this study, we found that the methanol extract of L. pustulata did not modify the frequency of the MN and nuclear division index in comparison to untreated cells (p > 0.05). These results revealed that the methanol extract had moderate free radical scavenging activity with IC(50) values of 395.56 μg/mL. Moreover, the extract tested had effective reducing power and superoxide anion radical scavenging. The values of the minimum inhibitory concentration against the tested microorganisms ranged from 0.625 to 20 mg/mL. In addition, the extract tested had strong anticancer activity against both cell lines with IC(50) values of 46.67 and 71.71 μg/mL.